Chaos-Induced Escape over a Potential Barrier - CHEW, L. Y. (Institutional Knowledge at Singapore Management University, 2004)
We investigate the statistical parity of a class of chaos-generated noises on the escape of strongly damped particles out of a potential well. We show that statistical asymmetry in the chaotic fluctuations can lead to a skewed Maxwell–Boltzmann distribution in the well. Depending on the direction of skew, the Kramers escape rate is enhanced or suppressed accordingly. Based on the Perron–Frobenious equation, we determine an analytical expression for the escape rate’s prefactor that accounts for this effect. Furthermore, our perturbative analysis proves that in the zeroth-order limit, the rate of particle escape converges to the Kramers rate.